ANALYSIS OF THE SOCIAL INCLUSION SITUATION IN LITHUANIAN NGO’S - Gerulaitis, Darius; Radzevičienė, Liuda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nongovernmental organizations are not just reinforcing the sense of sociality, but also permit to develop for the more universal inherent rights and abilities of a person: to extend the experience of a society while communicating with the people with disabilities, to create a social wealth with educational activities not for yourself but also and for others. The aim of a research is to reveal the principles of a social inclusion of people with disabilities but also and to reveal the assumptions in NGO's activities in Lithuania. The social model instead of a physical disability (also people that are treated as „problematic ones'“) failings suggested to identify the barriers that are socially contrasting in society (when people are facing difficulties). It was set up that one assumption of a successful activity of NGO is the ability of people with disabilities to cooperate that is also determined by peculiarities and motives of inter-communication of disabled, that encourages people for general activity. By the research there found factors that encourages and relieves the cooperation of people with disabilities: the content of NGO's activities and social openness and preparation to collaborate of NGO's members that are participating.